Perlindungan Investor terhadap Resiko Investasi Bodong Berkedok Pasar Modal - Alif Oemar Al Ghifari; Zulfikri Toguan; Oktavian Risnaldi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Fraudulent investment practices disguised as capital market activities have increasingly evolved through digital technology, social media, and online investment platforms, employing schemes such as illegal trading robots, fictitious stocks, and Ponzi mechanisms. Investor protection in Indonesia is implemented through preventive measures, including financial literacy programs, supervision of investment activities, and public disclosure of illegal investments, as well as repressive measures in the form of administrative and criminal sanctions against perpetrators. Using a normative legal method with statutory and conceptual approaches, this article relies on qualitative analysis of primary, secondary, and tertiary legal materials collected through literature review. The analysis demonstrates that the effectiveness of investor protection is closely related to public financial literacy, the supervisory role of the Financial Services Authority (OJK), the consistency of law enforcement, and the integration of digital monitoring systems. Weak public understanding of investment risks and the rapid expansion of technology-based financial services continue to create opportunities for fraudulent practices. Strengthening digital supervision mechanisms alongside expanding financial literacy initiatives remains essential to reduce the growth of fraudulent investments operating under the guise of capital market activities in Indonesia.